Transnational Commercial and Consumer Law Current Trends in International Business Law (Perspectives in Law, Business and Innovation, 2018)
This book explores current developments in transnational commercial and consumer law. It features essays written by leading experts, many of who have taken part in the negotiation and formulation of the international instruments they discuss here. The contributors look at issues arising from the profound changes that globalization is having on the legal norms governing commercial and consumer transactions, both domestic and transnational. They consider how relations between private actors, state regulators, and national courts are being completely reconfigured. This, in turn, generates pressures for legal harmonization and creates opportunities for new national and transnational legal norms and procedures to develop. The contributions address both the dynamics and the substance of these developments. Topics included are the UNCITRAL Model Law on secured transactions and on cross-border insolvency, the ICC Uniform Customs and Practices of Documentary Credits (UCP 600), and the dispute resolution mechanism and practices of the World Trade Organization. The content was formerly presented as papers at the 18th Biennial Meeting of the International Academy of Commercial and Consumer Law (the International Academy) at Kyushu University, Japan. Overall, this book provides readers with a solid theoretical foundation and strong familiarity with the practice of law and international commerce, offering realistic and practical conclusions.